EXPLORATION OF HETEROCYCLIC SCAFFOLDS USED TO TREAT PARKINSONISM: A REVIEW - MAYURA KALE; ASMITA AMBHORE (International Journal of Pharma and Bio Sciences, 2015)
Since past few decades, certain heterocyclic scaffolds have drawn special attention of medicinal chemists due to their biological potential and hence extensive efforts are being undertaken to search potential lead molecules through their design and synthesis. Heterocycles have also been actively involved to treat many neurodenegerative disorders, including Alzheimer’s disease, Parkinsonism and a few more. Although, there is currently no cure for Parkinson’s disease, but treatments are available to help relieve the symptoms and maintain quality of life of patients. In addition, there is no single drug available to relieve the patient completely from the copious symptoms of this disease. Hence, recent research has been focused on developing new molecules that will resolve all these related issues. The present review includes a rigorous literature survey on the various heterocycles exhibiting direct as well as indirect role in treating Parkinsonism.